Development of body temperature and its influence on the overall outcome in critically ill patients in the emergency department - Sládek, Jan; Rabasová, Pavlína (Vojenské zdravotnické listy, 2024)
Introduction: Thermoregulation is a complex process in the human body with the ability to maintain a constant optimal body temperature. Biochemical processes of the organism, as well as metabolic processes, are closely correlated with body temperature. Human temperature is determined by several laws, in particular metabolic production and heat flow between the organism and the environment. For the proper functioning of the organs in the human body, it is essential to maintain a constant optimum body temperature. This can be disturbed by inadequate internal and external factors and thermal discomfort can affect the patient's overall outcome. Aim: The aim of this study is to evaluate the development of body temperature in critically ill patients in the emergency department and its effect on overall patient outcome. Design: Quasi-experiment. Methods: Direct observation was performed, including measurement and analysis of body temperature in patients with serious condition in emergency admission. Data were collected in the emergency department of a teaching hospital with a trauma center status between March and December 2021. Statistical tests were evaluated at the level of statistical significance α=0.05. Results: The study population consisted of 274 (100%) patients. Most negative readings were recorded at the time of patient admission. During the course of treatment, there was a gradual adjustment of body temperature to the physiological limit. The resulting body temperature values were within the desired or expected parameters. In terms of a more detailed description, the most significant values were identified in patients with cardiac problems. Conclusions: Knowing the direction of body temperature skew can be considered beneficial. Early correction of pathological values can have a major effect on the overall outcome of the patient.
Keywords: Body Temperature Regulation; lidé; termoregulace; tělesná teplota; pozorovací studie jako téma; změny tělesné teploty; Body Temperature; Observational Studies as Topic; kritický stav; Body Temperature Changes; Critical Illness; Humans